Giovani a tempo indeterminato. Valori e atteggiamenti dei giovani romani - Di Franco, Giovanni (La cassetta degli attrezzi. Strumenti per le scienze umane - Open Access, 2017)
Being young in Italy in times of crisis means living with a mood that oscillates between depression and euphoria. Rather than thinking about the future, which is not known in any way, it is useful to look for some satisfaction in an eternal present time. The Italian young people's lives are suspended, invisible, lost, delayed, resized. They are those of an indefinite youth.